SPATIO -TEMPORAL DISTRIBUTION OF HIV/AIDS INFECTIONS IN ILORIN METROPOLIS, KWARA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
Understanding the epidemiology of HIV/AIDS in Ilorin metropolis is an issue of concern. Ameliorating this concern, the study examined certain objectives which are, to examine: the rate of HIV/AIDS infection in the metropolis; the demographic structure and characteristics of AIDS patients; the spatial distribution of the epidemic; as well as, evaluating the relationship between religion and spread of the infection in Ilorin metropolis. However, Secondary data collected from the University of Ilorin Teaching Hospital (UITH) were used. From these, an 8 year record consisting of 443 HIV/AIDS patients attached to the metropolis was studied. These were later analyzed using descriptive as well as inferential statistics. Thus, the result shows that females (63.2%) were more infected than the males (36.8%). Apart from this, those unmarried (singles) are less infected (32.5%), than the married (67.5%). Also, the non-civil servants (i.e. traders, artisans etc.) constitute the largest proportion (72.7%) of patients in the metropolis, from which majority (73.6%) are between ages 21-49 years. Also, education was found to exert significant influence on rate of infection, while the highest number of new cases (123 (27.8%) was recorded in year 2010. Sabon Geri ward II recorded the highest cases, while the least infected is Oju-ekun ward. In conclusion, the disease is found to be spatially inclined, coupled with the significant influence of age at first intercourse on exposure. It is recommended that, the government (at all levels) and relevant NGOs should accelerate policies and programmes development to reduce and ultimately eliminating HIV/AIDS infections in Ilorin.
Keywords: HIV/AIDS; Infections; Spatio-Temporal Distribution, Ilorin Metropolis